Pressure-induced phase transitions for goethite investigated by Raman spectroscopy and electrical conductivity. Issue 1 (2nd January 2019) - Liu, Kaixiang; Dai, Lidong; Li, Heping; Hu, Haiying; Zhuang, Yukai; Yang, Linfei; Pu, Chang; Hong, Meiling
ABSTRACT: We reported two pressure-induced phase transitions of goethite up to ∼35 GPa using a diamond anvil cell in conjunction with ac impendence spectroscopy, Raman spectra at room temperature. The first pressure-induced phase transition at ∼7.0 GPa is manifested in noticeable changes in six Raman-active modes, two obvious splitting phenomena for the modes and the variations in the slope of conductivity. The second phase transition at ∼20 GPa was characterized by an obviously drop in electrical conductivity and the noticeable changes in the Raman-active modes. The variations in activation energy with increasing pressure were also discussed to reveal the electrical properties of goethite at high pressure.